The organization of exhibitions as a kind of scientific-creative activity of the future artists-teachers - O.S. Yurchenko (Academy of Cognitive and Natural Sciences, 2006)
In the article a question is considered about the role of exhibition activity in the system of artistically-pedagogical education and councils are expounded of organization of artistic exhibition.